Hemifacial Spasm Caused by Distal Neurovascular Compression Confirmed by Lateral Spread Response Monitoring. Issue 8 (4th November 2022) - Xu, Xiaohui; Su, Sheng; Cai, Lingxin; Wang, Linkai; Fan, Haonan; Wu, Chunlai; Chen, Yili
Abstract : Primary hemifacial spasm (HFS) is likely related to a vascular compression of the facial nerve at its distal cisternal portion root exit Zone that has been reported during recent years. Most of these cases were found during secondary surgery or intraoperative monitoring of lateral spread response (LSR). Here we reported 2 patients with typical HFS caused by distal neurovascular compression that were successfully treated with microvascular decompression. Magnetic resonance imaging in both cases suggested that there was a contact between the vessel in cisternal segment and the facial nerve. LSR immediately disappeared after decompression of distal neurovascular compression. Resolution of spasm after the operation was achieved in both of these cases, with a short duration of vertigo and mild facial paralysis in case 1. Reviewing the literature, the majority of cases of distal neurovascular compression are found under the following 2 conditions:(1) When patients underwent a second operation. (2) When surgeons explored the distal part, the cisternal portion, after exploring the traditional root exit Zone without LSR disappearing. Therefore, it is the distal neurovascular compression at cisternal segment that may also be the cause of HFS. As for this kind of special HFS, these patients may also present with cranial nerve symptoms of VIII. In addition, magnetic resonance imaging can provide some information about compression sites. When we perform microvascular decompression, we should carefully pay attention to having an entire-root-exploration with intraoperative electrophysiology to find and decompress the real neurovascular compression.